Analisis Hubungan Tingkat Kesegaran Jasmani terhadap Hasil Belajar Siswa - Ikhwan Abduh; Humaedi Humaedi; Muhammad Agusman (Journal of Sport Science and Education, 2020)
Student academic problems have always been a concern of the government and teachers, various methods and design of learning that are used in improving academic achievement and student learning outcomes. This study examines the relationship of physical fitness to student learning outcomes. The number of samples 28 people selected from the population of 35 people with purposive sampling technique. Data collection techniques using 5 physical fitness test instruments and for learning outcomes taken from the results of midterm exams. Data analysis techniques used the Kolmogorof Smirnof One Sample Test and Pearson Spearman Correlation Test. The results showed that the highest physical fitness score of 24 was included in the very good category and the lowest score was 13, which means it was still lacking, the highest average student learning outcomes were 79.92 and the lowest average value was 72.28. While the Correlation analysis shows the value (r) 0.304 with a probability level (0.005) <Î±0.05 so there is a significant relationship between the two variables. Based on the analysis it is concluded that there is a relationship between the level of physical fitness with student learning outcomes, the better the physical fitness, the better the student learning outcomes will be.